Vivendo à margem: prevalência e vulnerabilidades ao transtorno mental comum em mulheres residentes em cidades rurais paraibanas - Furtado, Francisca marina de Souza Freire (2016)
The Common Mental Disorders (CMD) involves a set of signs and symptoms of non-psychotic nature, given its social, can be easily found in economically disadvantaged populations, especially among women. To have as a backdrop the small municipalities, this study has the thesis that poor living conditions when associated with issues such as gender inequalities and shortcomings in health services contribute to women of these locations are in vulnerability situations to CMD. In this sense, we aimed to analyze the main elements of vulnerability to CMD presented by women living in rural towns of Paraíba/Brazil. Two empirical studies were performed. The first epidemiological, transversal and quantitative aimed to identify the prevalence of CMD in women living in rural towns of Paraíba. With the participation of 608 women (mean age = 43 years old, SD=14.64) and the use of a socio demographic questionnaire and the Self-Reporting Questionnaire-20 (SRQ-20). The prevalence of CMD found among women was 31.6% and the most common symptoms related to somatic complaints and depression and anxiety symptoms. They were associated with the presence of CMD variables: family income lower than a minimum wage (χ2 (gl)=3,951(1); p=0.047); being a victim of domestic violence (χ2(gl)=20.987, p=0.001); experience of stressful situation (χ2(gl)=38.913, p=0.001) and family history with the same symptoms (χ2(gl)=12.304; p=0.001). Using logistic regression, it was as predictive variables for the CMD in the sample investigated a) being a victim of domestic violence (OR=2.58; CI95%=1:23 to 5:45); b) be experiencing stressful situation (OR=2.93; CI95%=1.85-4.65) and the interaction of variables c) have more than 50 years old and have a family history with symptoms of CMD (OR=3.96, CI95%=1.45-10.86) and d) having completed high school and have income between one and two minimum wages (OR=4.9, CI95%=1.44-11.66). In preliminary nature, the first study has point to the high CMD rate this among rural women and their relationship with socioeconomics and gender aspects. The second study, qualitative, cross-sectional, exploratory and analytical nature, aimed to analyze - from the account of the participants - which elements (individual, social and programmatic) vulnerability to the CMD are present in the experiences of women living in rural towns of Paraíba that contribute for those suffering with the CMD. With the participation of 10 women aged between 24 and 74 years old (M = 51.7, SD=18.1), using semi-structured interviews. These were analyzed using content analysis technique, using as support the Maxqda software version 11. The thematic categorization allowed to obtain two thematic classes: the first entitled "Scenarios rural of female suffering" made reference to the objective aspects of suffering and it involved six categories of analysis, namely a) Symptoms; b) Reasons for suffering; c) suffering the consequences; d) Self-care practices; e) Health care and f) mental health care. The second thematic class entitled "Rural female suffering experiences" made reference to the social and inter-subjective aspects of suffering and involved three categories of analysis, a) Marital Relationships; b) social support network and c) Rural Routine. Overall, the results showed that, in rural areas, the relationship between individual elements, social and programmatic walked down by gender inequalities associated with gender roles, in particular the role of mother to converge in vulnerable situations to CMD between rural women of Paraíba.